2003
DOI: 10.1093/ajcn/77.2.348
|View full text |Cite
|
Sign up to set email alerts
|

Human skin condition and its associations with nutrient concentrations in serum and diet

Abstract: Background: Nutritional factors exert promising actions on the skin, but only scant information is available on the modulating effects of physiologic concentrations of nutrients on the skin condition of humans. Objective: The objective was to evaluate whether nutrient concentrations in serum and diet are associated with the skin condition of humans. Design: A cross-sectional study was conducted in which data on serum concentrations of nutrients, dietary intake of nutrients, and the hydration, sebum content, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
67
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(88 citation statements)
references
References 34 publications
3
67
0
3
Order By: Relevance
“…1A. The stratum corneum water content in the control group was significantly lower at weeks 4,6,8,10, and 12 than week 0. In the collagen group, water content was significantly higher at week 2 and lower at week 10 than week 0.…”
Section: Methodsmentioning
confidence: 80%
See 2 more Smart Citations
“…1A. The stratum corneum water content in the control group was significantly lower at weeks 4,6,8,10, and 12 than week 0. In the collagen group, water content was significantly higher at week 2 and lower at week 10 than week 0.…”
Section: Methodsmentioning
confidence: 80%
“…In the collagen group, water content was significantly higher at week 2 and lower at week 10 than week 0. Twelve weeks of oral administration of collagen hydrolysate caused significantly higher values in water content compared with the control group at weeks 4,6,8,10, and 12. Skin elasticity data are shown in Fig.…”
Section: Methodsmentioning
confidence: 87%
See 1 more Smart Citation
“…No association between the nutrients in diet and sebum content of the skin have been found. However, increased serum vitamin A levels were related with decreased sebum content [12]. It has been suggested that caloric restriction can reduce sebum release.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the moisture value may also be affected by the type of consumed foods. One of the studies has shown that epidermal hydration is decreased as a result of the diet rich in saturated or monounsaturated fatty acids [43].…”
mentioning
confidence: 99%